Emotional reactions in the linguistic layer of diaries from the “times of plague” - Karwatowska, Małgorzata; Głażewska, Ewa (Papers in Linguistics, 2025)
Employing the method of qualitative content analysis, the authors of the study describe the feelings that people experienced during the COVID-19 pandemic as recorded in 24 pandemic diaries. The analyzed entries show not only strategies for coping with the new situation, but also exhibit very individual experiences. However, above all, they reveal the feelings of the diaries’ authors, decidedly dominated by negative, unpleasant emotions, such as anxiety, fear along with related feelings, but of varying degrees of intensity. All of these emotions were either directly verbalized or became apparent through external symptoms, i.e. the looks of the people experiencing them. When communicating their emotions, the senders used comparisons, metaphors, rhetorical questions, vulgar phrases or their euphemistic substitutes, as well as invective addressive phrases. Expressing strong feelings was also aided by the writers’ use of exclamations and, not infrequently, sentences in the imperative form. Vocabulary relating to colors also proved important in addressing the authors’ feelings.